Comparison of Histopathological Features of ‘Incidental’ and ‘Non-Incidental’ Papillary Thyroid Microcarcinomas - Kalita, Abhijit; Jojo, Annie; NV, Smitha (Annals of Pathology and Laboratory Medicine, 2019)
Background: Papillary thyroid microcarcinoma (Pm) is defined as a papillary carcinoma with size ≤ 10mm. On clinical and histological grounds, there are two presentations-‘incidental’ and ‘non-incidental’. Histopathological parameters like intratumoral/peritumoral fibrosis, multifocality, infiltrative borders, subcapsular location, lymphovascular emboli and histological type have been introduced in the reporting of Pm, besides the size which is considered an important prognostic/risk factor. Methods: The present study is a 5-year retrospective comparative study between the Pm which were incidentally detected, and those which had been previously diagnosed on fine needle aspiration/radiology or clinically suspicious of Pm. Result: The number of cases in both incidental (111) and non-incidental (110) Pm have been found to be comparable in the present study, which is attributable to meticulous grossing and extensive sampling of all thyroidectomy specimen. Size and multifocality has been significantly different between incidental and non-incidental Pm (p-value <0.05). The parameters like intratumoral/peritumoral fibrosis, infiltrative border and subcapsular location were significantly higher in larger sizes (>5mm) of non-incidental Pm (p-value <0.05). These parameters, however, were not found to be significant when analysed individually or with one another, between the two groups (p-value >0.05). In the incidental Pm of size ≤ 5mm, a good proportion of cases show these parameters, implicating their importance for further follow-up. Conclusion: Size and focality has been found to differ between incidental and non-incidental Pm. The histological parameters defined for Pm need to be followed up for a longer period to identify the prognostic significance, and their role in the different manifestation of incidental and non-incidental Pm.